2022
DOI: 10.1002/admi.202200501
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Stability Improvement with a High‐Performance PEALD‐IZO/IGZO Top‐Gate Thin‐Film Transistor via Modulating Dual‐Channel Effects

Abstract: Plasma‐enhanced atomic layer deposition (PEALD)‐based bilayer IZO (back channel)/IGZO top‐gate thin‐film transistors (TFTs) with different IZO and IGZO layer thicknesses are fabricated to evaluate the correlation between thickness and electrical characteristics/reliability caused by dual‐channel modulation. The dual‐channel formed by IZO stacked on the backchannel improves both mobility and reliability of devices as the IZO layer thickness increases. In the TCAD simulation, as the thickness of IZO increases, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…using TMA and H 2 O. This can cause a negative V th shift by generating additional electrons in IGZO. Figure (b) illustrates both the plausible mechanisms by which abnormal behavior can occur in positive gate bias.…”
Section: Resultsmentioning
confidence: 99%
“…using TMA and H 2 O. This can cause a negative V th shift by generating additional electrons in IGZO. Figure (b) illustrates both the plausible mechanisms by which abnormal behavior can occur in positive gate bias.…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, c-axis aligned crystalline IGZO (CAAC-IGZO) reported by the Semiconductor Energy Laboratory (SEL) exhibited high mobility (50 cm 2 V −1 s −1 ), extremely low off-current (∼10 −24 A µm −1 ) and enhanced bias stability, but it was necessary to increase the process temperature up to 800 • C [13]. A double active layer [14], back-channel treatment [15], and front-channel modulation [16] of TFTs were studied to optimize device properties. In addition to these studies, TFT structure optimization [17], interface engineering [18], post-treatment [19], and anion doping [20] were also investigated to improve the mobility and stability of oxide semiconductors.…”
Section: Recent Progress In Oxide Semiconductors For Thin-film Transi...mentioning
confidence: 99%
“…With the growing interest in ALD, studies on materials using ALD have also rapidly increased, as shown in the table, which will be discussed in this review. In particular, superior electrical performances have been recently reported, including a remarkable mobility of over 100 cm 2 V −1 s −1 [43,46], an exceptionally low subthreshold swing under 100 mV/decade [64,66,80,83], and highly improved stability using a stack structure [14]. However, the main benefits of employing ALD for oxide semiconductor channel TFTs have not been clearly suggested.…”
Section: Value Of Ald As a Fabrication Process For Oxide Semiconducto...mentioning
confidence: 99%
“…They confirmed that efficient thickness control using ALD is a promising strategy for fabricating high-mobility and high-reliability heterojunction oxide TFTs. 56…”
Section: Heterojunction Oxide Tftmentioning
confidence: 99%